The Effect of Brand Image and Relationship Quality on Patient Satisfaction - Al Maududi, Abul A'la; Jaksa, Suherman (Siber Journal of Advanced Multidisciplinary, 2024)
This study aims to determine and analyze the effect of brand image and relationship quality on the satisfaction of outpatients of Hermina Pasteur Bandung Hospital. The results of this study are expected to be input for Hermina Pasteur Hospital in organizing health services, especially in increasing satisfaction. The research method used is descriptive and verification analysis. Data collection used is an interview using a questionnaire accompanied by observation techniques and literature, sampling using consecutive sampling. Data collection in the field was carried out in 2023. Data analysis techniques using Path Analysis. The results showed that in general, brand image, relationship quality, and patient satisfaction tend to be quite good. There is an influence of brand image and relationship quality on patient satisfaction both simultaneously and partially at Hermina Pasteur Hospital. Hermina Pasteur Hospital must carry out service recovery for patient complaints or complaints quickly, so as not to cause dissatisfaction from patients, to handle patient complaints quickly the hospital can form a customer care program